Influence of Available Bandwidth on the Statistical Characterization - Bahl, Victor (1996)
The design and analysis of robust networking protocols that offer useful performance guarantees requires accurate traffic source models. In this paper we study the problem of characterizing and modeling the arrival process of compressed video. We extend earlier works in this area by including a factor that has previously been ignored, the effect of video capture rate on traffic characterization.
University of Massachusetts, ECE Dept. Technical Report, TR-CSE-7 (February 1996)